Critical Thinking Skills and Argumentative Writing Ability:Is there any Correlation? - Yulian Juita Ekalia; Fransiskus Jemadi; Indra Susanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores the relationship between critical thinking skills and argumentative writing ability among eleventh-grade students at SMAK Fransiskus Xaverius Ruteng. In the Indonesian educational context, students often face challenges in producing well-structured and logically supported arguments, partly due to limited emphasis on critical thinking in traditional teaching methods. Argumentative writing requires not only language proficiency but also the ability to analyze, evaluate, and synthesize information. This research aims to determine whether a significant correlation exists between these two essential academic competencies. The study employed a quantitative correlational research design involving 30 students from the Language Program. Critical thinking skills were measured using the Watson-Glaser Critical Thinking Appraisal (WGCTA), while argumentative writing ability was assessed through a standardized writing test evaluated by a rubric. Data analysis using Pearson’s Product-Moment Correlation and SPSS Version 25 revealed a very strong positive correlation (r = 0.813) between critical thinking and argumentative writing. The coefficient of determination (R² = 0.661) indicated that 66.1% of the variance in writing performance can be attributed to critical thinking abilities, while the remaining 33.9% is influenced by other factors such as language proficiency and prior writing experience. The findings confirm a significant positive correlation between critical thinking and argumentative writing, supporting the integration of critical thinking strategies into writing instruction. Students with higher critical thinking scores generally produced more coherent, logical, and persuasive texts. The study suggests that educators should incorporate techniques such as argument mapping, debates, and peer review sessions to enhance both cognitive and linguistic development.